Lethal autonomous weapons systems, revulsion, and respect - Dean, Richard (Frontiers in Big Data, 2022)
The potential for the use of artificial intelligence in developing lethal autonomous weapons systems (LAWS) has received a good deal of attention from ethicists. Lines of argument in favor of and against developing and deploying LAWS have already become hardened. In this paper, I examine one strategy for skirting these familiar positions, namely to base an anti-LAWS argument not on claims that LAWS inevitably fail to respect human dignity, but on a different kind of respect, namely respect for public opinion and conventional attitudes (which Robert Sparrow claims are strongly anti-LAWS). My conclusion is that this sort of respect for conventional attitudes does provide some reason for actions and policies, but that it is actually a fairly weak form of respect, that is often override by more direct concerns about respect for humanity or dignity. By doing this, I explain the intuitive force of the claim that one should not disregard public attitudes, but also justify assigning a relatively weak role when other kinds of respect are involved.